A single-center experience with continuous and pulsatile flow veno-arterial extracorporeal membrane oxygenation for cardiogenic shock - Lindner, Simon; Steffen, Henning Johann; Akın, Ibrahim; Jabbour, Claude; Dürschmied, Daniel; Helbing, Thomas; Britsch, Simone (Cardiology, 2025)
Introduction: Pulsatile flow in veno-arterial extracorporeal membrane oxygenation (VA-ECMO) for the treatment of cardiogenic shock may yield physiological benefits over continuous flow. The primary objective of this study was to evaluate whether there are detectable differences between these modes in a small single-center cohort. Methods: We performed a retrospective analysis of patients who underwent VA-ECMO support for cardiogenic shock at our institution between 2019 and 2023. Data collected included demographic information, disease severity scores, duration of ECMO support, and duration of pulsatile flow. Primary outcome variables were in-hospital mortality and Barthel score. Safety outcomes were stroke or systemic embolization, bleeding, and limb ischemia. Results: A total of 66 patients were included in the analysis. Seventeen (26%) had received continuous and 49 (74%) pulsatile VA-ECMO. In-hospital mortality was 71% vs. 80% (p = 0.445) and mean Barthel scores in survivors were 85 vs. 71 (p = 0.488). All safety outcomes were similar between the groups. In VA-ECMO devices capable of pulsatility, actual pulsatile flow was delivered during 64% of total runtime. Conclusion: We could not demonstrate clear differences in mortality or functional outcome between pulsatile and continuous flow in this single-center cohort. However, the small sample size, short time of actual pulsatile flow, and several between group differences clearly limit the robustness of this observation. The inconclusive nature of our results underscores the need for larger and randomized controlled trials.
Gesehen am 31.07.2025